Novel medicinal plants uses for the treatment of respiratory disorders - An overview from Madyan Swat, Pakistan - Dilbar, Shazia; Sher, Hassan; Ali, Ahmad; Ullah, Zahid; Shuaib, Muhammad; Yaseen, Muhammad; Bahadur, Saraj (Ethnobotany Research and Applications, 2023)
Background: Rural people living in Madyan Valley, Swat, Pakistan, rely extensively on medicinal plants for treating respiratory chest infections, cough, cold, asthma and bronchitis. Therefore, the present aims to identify specific medicinal plants for the treatment of respiratory diseases and analysis of different types of preparation for relieving respiratory ailments. Methods: Accordingly, men and women were interviewed using medicinal herb data sheets, supplemented with a transect walk. Uses, modes of preparation, storage and collection habitats of individual plants used for treating respiratory disorders were identified and recorded. Medicinal plants’ natural habitat provided a platform to further explore the active medicinal properties unknown to the community. Medicinal plant data were quantitatively measured using measurement models such as relative frequency citation (RFC); use value (UV) and fidelity level (FL). Results: The study recorded fifty-one plant species belonging to 32 families used for relieving respiratory diseases. Lamiaceae was the largest family with six species followed by Asteraceae and Apiaceae. About 30% of women knew the active medicinal properties, compared to 53% of men. The elderly women who had a deeper knowledge of plant remedies dispensed the plants in infusions, decoctions, and syrups; however, the most common form of intake was sundried powder typically administered with water. Conclusions: Herbal treatments in Northern Pakistan are reliable, inexpensive alternatives for treating respiratory conditions. We recommend appropriate management and the promotion of the cultivation and conservation of medicinal plants. In addition, raising awareness of the importance of medicinal plants for respiratory conditions must be established. Keywords: Medicinal plants, herbal preparations, respiratory diseases, traditional medicine, Northern Pakistan